Phospholipid-Based Microemulsions for Cutaneous Imiquimod Delivery - Panoutsopoulou, Eleni; Zbytovská, Jarmila; Vávrová, Kateřina; Paraskevopoulos, Georgios (Pharmaceuticals (Basel, Switzerland), 2022)
Imiquimod (IMQ) is a potent immune response modifier with antiviral and antitumor properties. IMQ's low aqueous solubility and unsatisfactory cutaneous permeability limit its formulation into effective dosage forms. This work aimed to develop IMQ-loaded microemulsions (MEs) based on phospholipids and oleic acid to improve IMQ penetration into the epidermis. A pseudo-ternary phase diagram was constructed, and the microstructure of the formulations was examined by measuring the conductivity values. Selected MEs were characterized and studied for their ability to deliver IMQ into and through ex vivo human skin. ME1 with 1% IMQ (bicontinuous ME with Bingham rheology) delivered similar IMQ quantities to the human epidermis ex vivo as the commercial product while having a 5-fold lower IMQ dose. IMQ was not detected in the acceptor phase after the permeation experiment, suggesting a lower systemic absorption risk than the established product. Infrared spectroscopy of the stratum corneum revealed less ordered and less tightly packed lipids after ME1 application. The ME1-induced barrier disruption recovered within less than 5 h after the formulation removal, as detected by transepidermal water loss measurements. In conclusion, our findings demonstrate that phospholipid and oleic acid-based MEs could become a promising alternative for topical IMQ administration.
Keywords: oleic acid; transepidermal water loss; imiquimod; microemulsions; infrared spectroscopy; dermal delivery